Peran Negara dalam Pemberian Bantuan Hukum bagi PMI yang Terjerat Kasus Hukum di Luar Negeri (Studi Perbandingan antara Indonesia dan Filipina) - Abdul Mustopa Jawahid; Nanda Hairunnisa (Fakultas Hukum Universitas Islam Indonesia, 2025)
Indonesian Migrant Workers (PMI) have long been a vital pillar of the national economy through their contributions as foreign exchange earners. However, several issues remain, particularly the lack of legal assistance for PMI involved in legal cases abroad, as well as the non-procedural status of some PMI, who are indirectly unrecognized and excluded from the scope of protection under the Indonesian Migrant Workers Protection. In contrast, the Philippines has a clearer legal assistance system that does not distinguish between the legal or illegal status of its workers. The issue that arises in this study is how Indonesia and the Philippines can provide legal assistance to their migrant workers who encounter legal problems abroad, as well as identifying the substance of regulations in the Philippines that can be applied in Indonesia. This research uses a normative legal method with conceptual, statutory, and comparative approaches. The results show that the Philippines outperforms Indonesia in three aspects: first, a more comprehensive concept of protection and social security; second, stronger and more inclusive legal protection and assistance for migrant workers; and third, more robust welfare and training support programs. Substantive models that can be adopted in Indonesia include the MWOFRC, LAMWA, and LAF.